EFEKTIVITAS INFUSA JAHE MERAH (ZINGIBER OFFICINALE VAR. RUBRUM) SEBAGAI ANTIDIARE PADA MENCIT PUTIH JANTAN YANG DI INDUKSI OLEUM RICINI DENGAN METODE TRANSIT INTESTINAL - Yulis Azizah; Rizka Mulya Miranti; Dedi Hartanto; Retna Eka Dewi (Journal of Innovation Research and Knowledge, 2023)
Red ginger is a plant of the Zingiberaceae family which contains active compounds which are consider to have a major contribution to the anti-diarrheal effect are steroids, tannins, flavonoids, and saponins. The purpose of this study was to determine if red ginger infusion has an antidiarrheal effect and what is the effective dose if it has an anti- diarrheal effect. This research is an experimental with a Completely Randomised plan (CRP) with a one way model. Twenty-four mice were randomly assigned to 6 groups of 4 mice within each group. The Red ginger infusion was tested with 3 different dosage variations; 1.047 g/kgBW, 2.095 g/kgBW, and 4.19 g/kgBW. The Antidiarrheal activity in this study was determined by computing the ratio of the bowel length passed through the marker to total length of the intestine. The results showed that red ginger infusion has an anti-diarrheal effect. Infusion of red ginger at doses of 1.047 g/kg BB, 2.095 g/kg BB and 4.19 g/kgBW, resulting in average ratios of 0.596, 0.37975 and 0.164125, consecutively. Based on a statiscal data analysis with the Mann Whitney Test, it was obtained that the ratio between a dose of 4.19 g / kgBW and the Loperamide comparison group of 4 mg / kgBW dose did not have a meaningful difference. So the most effective dose of red ginger infusion as an anti-diarrhea is 4.19 g/kgBW.